INTERNAL CULTURAL ENVIRONMENT AND PSYCHOLOGICAL EMPOWERMENT ON EMPLOYEE ENGAGEMENT MEDIATED BY EMPLOYEE PERSPECTIVE OF GENERATION Z EMPLOYEES IN THE MM 2100 INDUSTRIAL AREA BEKASI REGENCY - Nuraeni, Winda; Purwani Setyaningrum, Retno (Jurnal Ilmu Manajemen (JIMMU), 2025)
This study was conducted to explore the extent to which Cultural Environment Factors and Psychological Empowerment influence Employee Engagement, with Employee Perspective as a mediating variable. The research employed a quantitative approach using a causal-explanatory research design. Data analysis was carried out using the Lemeshow formula and the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique, executed through the SmartPLS 4.0 software. Respondents were selected randomly using the Simple Random Sampling method. The results of the study indicate that Employee Engagement has a significant effect on Employee Perspective. Internal Cultural Environment significantly affects Employee Engagement, but does not have a direct significant effect on Employee Perspective. Psychological Empowerment was found to have a significant effect on both Employee Engagement and Employee Perspective. Furthermore, the study revealed a significant indirect effect of Internal Cultural Environment on Employee Perspective through Employee Engagement, as well as an indirect effect of Psychological Empowerment on Employee Perspective through Employee Engagement. These findings highlight the critical mediating role of Employee Engagement in shaping Employee Perspective.